ANALYSIS OF ISLAMIC SUBJECT TEST QUALITY USING THE ITEM RESPONSE THEORY OF RASCH MODEL - Alfi Faroh Kamaliya; Sri Sumarni; Himawan Putranta; Apriliana Indah Lestari; Fatma Nurhayati; Nely Anggraeni Ayuningtiyas (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
The objective of this study is to use the Rasch Item Response Theory (IRT) approach to assess and characterize multiple choice exams and AKM Islamic Religious Education Subjects developed by students. This is a descriptive quantitative study that included 30 student replies to multiple choice test instruments and AKM with five possible solutions. The Rasch Model Item Response Theory (IRT) technique was used to analyze quantitative data using the QUEST program and the content validity instrument by constructing the Aiken's V formula. The study revealed that 13 items fit, 2 items did not fit, and all items were valid. The reliability coefficient on the item summary shows the "enough" criteria and the reliability coefficient on the estimation case summary shows the "weak" criteria, the item difficulty level shows 13 items in the good category and 2 items in the poor category, and the results of validation by experts processed by experts using the Aiken's V formula show that all items are classified as valid.